Strategi Pembinaan Kondisi Fisik dalam Menurunkan Risiko Cedera pada Pemain Bola Voli - Sahabuddin; Hudain, Muh. Adnan; Awaluddin, Awaluddin (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2025)
This study examines the effectiveness of physical conditioning coaching strategies in reducing the risk of injury in volleyball players at BKMF Bolavoli FIKK UNM. The method used was a quasi-experimental one-group pre-test post-test design. The sample consisted of 30 athletes with an average age of 20 years. The training program included increasing endurance, muscle strength, agility, and explosive power for 8 weeks. The results showed a significant increase in physical condition: 12-minute running endurance increased from 2200 m to 2500 m, push-ups from 25 to 35 repetitions, sit-ups from 30 to 42 repetitions, shuttle run from 15.2 seconds to 13.8 seconds, and vertical jump from 35 cm to 42 cm (p <0.05). The risk of injury decreased by 40%, from 15 to 9 incidents. These findings confirm that structured physical conditioning coaching is effective in improving performance and reducing injuries in volleyball athletes. Periodic injury monitoring and evaluation are recommended for program sustainability.